Proceedings of the International Conference on Economics, Management and Technology in Enterprises 2019 (EMT 2019) 2019
DOI: 10.2991/emt-19.2019.6
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Behaviour in Conditions of Dual Quality of Daily Consumption Goods in Slovakia

Abstract: The problem of dual quality of daily consumption goods in the countries of the European Union has been known for a while. Well-known manufacturers do not offer their products in the same composition and quality in all countries of the join European market but produce two variants. The first variant for Western countries includes other basic and auxiliary ingredients, other proportions of basic raw materials, other active ingredients, as the second variant designated for the countries of Central and Eastern Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…These findings provide various ideas for possible solutions to this problem that would suit this specific consumer segment. Some researches confirm that consumers (including those in Slovakia) increasingly prefer quality over price when buying goods, especially food products (GfK, 2008;GfK, 2015;KuSnírova, 2016;GfK, 2017;Bartkova et al, 2018). In turn, this research's findings indicated that this fact also applies to the Millennial generation, for which the quality at the time of purchase is more important than the price of the goods.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…These findings provide various ideas for possible solutions to this problem that would suit this specific consumer segment. Some researches confirm that consumers (including those in Slovakia) increasingly prefer quality over price when buying goods, especially food products (GfK, 2008;GfK, 2015;KuSnírova, 2016;GfK, 2017;Bartkova et al, 2018). In turn, this research's findings indicated that this fact also applies to the Millennial generation, for which the quality at the time of purchase is more important than the price of the goods.…”
mentioning
confidence: 62%
“…These hypotheses were formulated based on previous research studies conducted on the issue of dual quality perceptions (Bartkova et al, 2018;Bartkova, 2019;Bartkova et al, 2019;Veselovska, 2020). However, these surveys focused on customers of all age segments without distinguishing the differences in consumer behaviour that age could create.…”
mentioning
confidence: 99%